Echanges between the Arctic Ocean and the North Atlantic: Origin, variability and impact in the Nordic Seas. - Lique, Camille (HAL CCSD, 2010)
While perhaps the most obvious, ice retreat is just one aspect of a changing Arctic system. The Arctic Ocean is also undergoing unprecedented modifications, that mostly affect its heat and freshwater budgets. As the signal of Arctic change is expected to have its major climatic impact by reaching south the subarctic seas, on either side of Greenland, to modulate the Atlantic thermohaline circulation, the objective of this thesis is to investigate the variability of the exports of volume, heat, freshwater and sea-ice from the Arctic Ocean to the North Atlantic. First, a realistic simulation from 1958 to 2002 run with a global ocean/sea-ice model is used to investigate some aspects of the variability of the Arctic freshwater budget, trying to understand which component of the balance is responsible for the variability of the Arctic freshwater content. We also examine the variability of the freshwater exports to the North Atlantic and we find that this variability is controlled differently on both sides of Greenland: whilst freshwater transport variations across Davis Strait are completely determined by the variations of the total volume flux, the salinity variations due to the ice ocean flux north of Greenland are responsible for a significant part of the freshwater export variability through Fram Strait. Afterward, a simulation run with a fully assimilated model of the very recent period is used to explore the possible consequences of the 2007 sea ice extent minimum on the Arctic Ocean freshwater content. Then, the origins of the water masses exported from the Arctic to the North Atlantic along both sides of Greenland are investigated, using an original numerical method. A quantitative Lagrangian analysis is applied to the monthly climatological 3D output of a global ocean/sea-ice high resolution model. It allows quantification of the different branches of the export to the North Atlantic, as well as related timescales and water mass transformations. A complete and coherent scheme of circulation for the Arctic is ...